2014
DOI: 10.4082/kjfm.2014.35.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Association between Appendicular Fat Mass and Metabolic Risk Factors

Abstract: BackgroundDifferent regional fat depots have different effects on lipid and glucose metabolism. The purpose of this study is to examine the relationship between body fat distribution as measured by dual-energy X-ray absorptiometry (DEXA) and metabolic risk factors and to disclose whether there is any difference between groups with and without metabolic syndrome (MS).MethodsA total of 292 participants (98 men, 194 women) over 19 years old underwent whole-body DEXA to evaluate body composition with respect to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…Pathophysiological relevance to assess appendicular regional fat and muscle distribution would be revealed in the fact that greater fat mass distributed in appendicular sites, such as lower limbs, appears to be beneficial or protective against cardiovascular disease and/or metabolic risk factors as compared with central obesity (Hu et al 2011 ; Park et al 2014 ; Snijder et al 2009 ). These protective effects of appendicular fat might be mostly attributed to the leg, especially thigh (Hunter et al 2010 ; Park et al 2014 ; Snijder et al 2005 ). On the other hand, the study using DEXA to evaluate percentage of fat has shown less impact of upper limbs on diagnosing metabolic disease compared to lower limbs (Park et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiological relevance to assess appendicular regional fat and muscle distribution would be revealed in the fact that greater fat mass distributed in appendicular sites, such as lower limbs, appears to be beneficial or protective against cardiovascular disease and/or metabolic risk factors as compared with central obesity (Hu et al 2011 ; Park et al 2014 ; Snijder et al 2009 ). These protective effects of appendicular fat might be mostly attributed to the leg, especially thigh (Hunter et al 2010 ; Park et al 2014 ; Snijder et al 2005 ). On the other hand, the study using DEXA to evaluate percentage of fat has shown less impact of upper limbs on diagnosing metabolic disease compared to lower limbs (Park et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These protective effects of appendicular fat might be mostly attributed to the leg, especially thigh (Hunter et al 2010 ; Park et al 2014 ; Snijder et al 2005 ). On the other hand, the study using DEXA to evaluate percentage of fat has shown less impact of upper limbs on diagnosing metabolic disease compared to lower limbs (Park et al 2014 ). It is possible, however, that DEXA- or BIA-derived percentage of fat does not reflect site-specific fat and muscle distribution, thereby missing the association between regional limb composition and diagnostic criterion.…”
Section: Discussionmentioning
confidence: 99%
“…Fat within the abdominal region, in adults, is more strongly related with metabolic complications than total excess body fat (Despres & Lemieux, 2006). In contrast, adipose tissue located at peripheral sites, such as the thigh and legs, appears to be protective against metabolic syndrome (Park et al, 2014). Moreover, in adults, subcutaneous fat appears to be less metabolically deleterious than fat distributed within visceral depots or within muscle (Bastien et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent findings could be due to multiple factors such as the fat depot studied, the metabolic biomarkers assessed, variation in total body fat, and the ethnicity of the population being studied. It has been suggested that the amount and location of fat depots may have differential relationships with different risk factors (Park et al, 2014; Sanchez-Lopez et al, 2013). For example, Samouda et al found that visceral adipose tissue had significant positive correlations with triglycerides (TG) and high density lipoprotein cholesterol (HDL-C), whereas leg fat mass did not have a significant correlation with TG, but had a significant positive correlation with HDL-C in overweight and obese children (Samouda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we explain the assumptions in the analysis of covariance and the relationship between the magnitudes of correlation coefficient and P-value, which appeared in the articles titled, "Association between nutrition label reading and nutrient Intake in Korean adults: Korea National Health and Nutritional Examination Survey, 2007-2009 (KNHANES IV)," by Kim et al 1) and "Association between appendicular fat mass and metabolic risk factors," by Park et al 2) published in July 2014.…”
mentioning
confidence: 99%